Toward a New Model of Science Learning, Teaching, and Communication. Issue 56 (5th February 2016) - Adetunji, Oludurotimi O.; Levine, Roger
ABSTRACT: Sci-Toons is a new, experimental, teaching and learning approach that engages students in materials science research via interaction with experts, narrative, visual representations, iterative feedback and multimedia platforms. Based on a model (the Multimedia Theoretical Learning Framework) and multimedia design principles, Sci-Toon Creation Group (SCG) members, which include both science and non-science majors, work with faculty to produce video animations dealing with scientific topics. The creative process of producing scripts for two selected Sci-Toons videos dealing with materials science subjects (Graphene and Conductive Polymers) are discussed; initial and final versions of each are combined through use of Word Clouds. The videos that are produced are distributed via the internet, providing instruction and information about materials sciences and other STEM topics. Demographic data about the types of individuals downloading these Sci-Toons are provided. We conclude that Sci-Toons can be used in both formal and informal educational settings for science learning and teaching as well as in communicating materials science concepts to broad audiences including females and underrepresented minorities students.